PRONUNCIATION MADE EASY: LEVERAGING VOCABULARY PLATFORMS FOR CLEARER SPEECH - Wahid, Jusmin HJ. Wahid; Irawan, Iwan; Djafar, Hariyanti; Pagama, Nurwahda (Penerbit Lafadz Jaya, 2025)
The aim of this research is to determine the effect of using the English Vocabulary platform on the pronunciation abilities of the second grade of SMP Al-Khairaat Wayaua. The researchers used quantitative research methods using a one shot case study research design. This research instrument is multiple choice and consits of 50 questions. In analyzing data, the researchers used SPSS-21 to analyze descriptive data to determine students categories and inferential analysis to determine normality, homogenity, and hypothesis tests. The findings showed that the effect of implementing the English Vocabulary platform in the learning and teaching process improve students' pronunciation as well. The researchers concluded that the platform of English vocabulary can have a good influence on the use of pronunciation at second grade students of SMP Al-Khairaat Wayaua. Therefore, the researchers recommend that English teachers should implement the English Vocabulary platform as a medium for teaching and learning English process.